Surface Water Contamination Due to Industrial Activities in Gebeng Area, Kuantan, Malaysia - Islam, Mir Sujaul; Sobahan, Md Abdus; Ideris, Zakaria; Hossain, Mohamed Amjed (2013)
Gebeng is a rapidly growing industrial area of Kuantan, Pahang, Malaysia. The water bodies are being affected by anthropogenic activities. Industrial effluents and waste water having contaminants are incorporated with river water regularly. The study was carried out to explore the pollution level and to find out human interference on river water quality. To conduct the research, surface water was collected from 10 different strategic locations of the river. The physico-chemical characteristics of water including temperature, pH, electrical conductivity, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), total dissolved solids (TDS), total suspended solids (TSS), turbidity, nitrate, ammonia-cal-N, phosphate, sulphate and some selected heavy metals were measured by using standard methods. Statistical analyses were done by using SPSS software (version 16.0). The study showed that heavy metals such as Pb, Cu, Co, Cd and As concentrations were higher at station 4, 5, 6, 7 and 8 and more polluted, and at the downstream station 8, 9 and 10 were less polluted due to tidal interference. According to DOE-INWQS all stations were categorized as polluted (Class III to and V). Moreover, the most affected parameters were pH, DO, COD, BOD, ammonical nitrogen, nitrate and phosphate. Human activities especially treated and untreated industrial wastes as well as the effluents from the point and non- point sources increased the contamination levels of the studied surface water.